Author Correction: Suicide among cancer patients - Zaorsky, Nicholas G.; Zhang, Ying; Tuanquin, Leonard; Bluethmann, Shirley M.; Park, Henry S.; Chinchilli, Vernon M. (Nature communications, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.An amendment to this paper has been published and can be accessed via a link at the top of the paper.